AN ANALYSIS OF INTERCULTURAL COMMUNICATIVE COMPETENCE IN EFL TEXTBOOK OF GRADE TWELFTH OF HIGHSCHOOL - Elin Wahyuni; Melati; Nely Arif (Universitas Jambi, 2022)
The aims of this research were to discover how the communicative competence is represented and to examine how intercultural communicative competence is promoted in EFL textbook “Bahasa Inggris” for Twelfth Grade. Dealing with textbook analysis, this research applied content analysis with a qualitative approach. The data were analyzed based on five steps; observation, marking checklist, classifying, coding, and interpretation. The finding of research revealed that the learning task in the textbook represented four component of communicative competence and predominated by Linguistic. Moreover, the four elements of Intercultural Competence were well covered but less then the other competence, with the dominance of knowledge aspects. Thus, based on this finding, hopefully the textbook will be developed more to assist students in building their Intercultural Communicative Competence.